Phenomenological experience of interview with users of crack: an experience report - Fernando Jose Guedes da Silva; Claudete Ferreira de Souza Monteiro (Universidad de Alicante, 2012)
The aidms of this paper is to describe the experience of one of the authors in obtaining reports of crack users using the phenomenological interview. Walk in this process were considered key strategies for approaching the subject of this study, since they supported the familiarity and empathy researcher-subject to this overriding methodological strategy. This manifested itself as a strategy for the seizure of intrinsic meanings about death and dying for user-to-be-crack. Obtaining reports reflect the experience of them in the consumption of crack cocaine led to the fact that the absence of an existential sense, one can be and being in the world.